The general dynamic model: towards a unified theory of island biogeography? - Borregaard, M; Matthews, T; Whittaker, R (Wiley, 2015)
Aim Island biogeography focuses on understanding the processes that underlie a set of well-described patterns on islands, but lacks a unified theoretical framework for integrating these processes. The recently proposed General Dynamic Model (GDM) of oceanic island biogeography promises a step towards this goal. Here, we present an analysis of causality within the GDM, and investigate its potential for the further development of island biogeographical theory. Further, we extend the GDM to include subduction-based island arcs and continental fragment islands. Location Based on conceptual analysis and a simulation of oceanic islands. Methods We describe the causal relationships between evolutionary and ecological processes implied by the GDM, implement them as a computer simulation, and use this to simulate two alternative geological scenarios. Results The dynamics of species richness and rates of evolutionary processes in simulations derived from the mechanistic assumptions of the GDM corresponded broadly to those initially suggested, with the exception of trends in extinction rates. Expanding the model to incorporate different scenarios of island ontogeny and isolation revealed sensitivity of evolutionary dynamics on attributes of island geology. Main conclusions We argue that the General Dynamic Model of oceanic island biogeography has the potential to form a unified framework of island biogeography, integrating geological, ecological and evolutionary processes. Our simulations highlight how the geological dynamics of distinct island types are predicted to lead to markedly different evolutionary dynamics. This sets the stage for a more predictive theory incorporating the processes governing temporal dynamics of species diversity on islands.